THE EFFECT OF EXPERIENCE OF SHOPPING AND PERCEPTION OF PRICE ON PERCEPTION OF QUALITY AND PERCEPTION OF VALUE : A CASE STUDY IN SHOPPING CENTER OF MALL PARAGON SOLO, CENTRAL JAVA - achmad Choerudin; Margaretha Martina Budhi Utaminingsih (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2017)
The research aims to the effect of experience of shopping and perceived of price on perceived of quality and  perceived of value in the shopping center in Mall Paragon Solo, central Java, Indonesia. The collecting data was  questionnaires and observations. The sampling was used an accidental sampling of nonprobability sampling technique. The analysis of data using regression.  The results of research were (1) the experience of shopping has a negative effect and insignificant on perception of quality, (2) the perception of prices has a negative effect and insignificant on perception the quality, (3) the experience of shopping has a positive effect and significant on perception of value, and (4) the perception of prices has a positive effect and significant impact on perception of value as well as (5) the perception of quality has a negative effect and insignificant on perception of value.